Linked Color Imaging and Blue Laser Imaging for Upper Gastrointestinal Screening - Hiroyuki Osawa; Yoshimasa Miura; Takahito Takezawa; Yuji Ino; Tsevelnorov Khurelbaatar; Yuichi Sagara; Alan Kawarai Lefor; Hironori Yamamoto (Korean Society of Gastrointestinal Endoscopy, 2018)
White light imaging (WLI) may not reveal early upper gastrointestinal cancers. Linked color imaging (LCI) produces bright images in the distant view and is performed for the same screening indications as WLI. LCI and blue laser imaging (BLI) provide excellent visibility of gastric cancers in high color contrast with respect to the surrounding tissue. The characteristic purple and green color of metaplasias on LCI and BLI, respectively, serve to increase the contrast while visualizing gastric cancers regardless of a history of Helicobacter pylori eradication. LCI facilitates color-based recognition of early gastric cancers of all morphological types, including flat lesions or those in an H. pylori-negative normal background mucosa as well as the diagnosis of inflamed mucosae including erosions. LCI reveals changes in mucosal color before the appearance of morphological changes in various gastric lesions. BLI is superior to LCI in the detection of early esophageal cancers and abnormal findings of microstructure and microvasculature in close-up views of upper gastrointestinal cancers. Excellent images can also be obtained with transnasal endoscopy. Using a combination of these modalities allows one to obtain images useful for establishing a diagnosis. It is important to observe esophageal cancers (brown) using BLI and gastric cancers (orange) surrounded by intestinal metaplasia (purple) and duodenal cancers (orange) by LCI.